Criminal Justice Decision Making as a Stratification Process: The Role of Race and Stratification Resources in Pretrial Release - Albonetti, Celesta Ann (1989)
Our purpose is to bridge the criminal justice and stratification research literatures and to pursue the argument that homologous structural principles stratify allocation processes across central institutions of American society. The principle observed here in the making of bail decisions, as in earlier studies of the allocation of earnings, is that stratification resources operate to the greater advantage of whites than blacks. The operation of this principle is established through the estimation of covariance structure models of pretrial release decisions affecting 5660 defendants in 10 federal courts. Education and income are treated in this study as observed components of a composite construct, stratification resources, which works to the greater advantage of whites. Prior record is also found to operate to the greater advantage of whites. Two further variables, dangerousness and community ties, increase bail severity among blacks and whites. While the effect of community ties has been legally legitimized since the Bail Reform Act of 1966, the effect of dangerousness was not so legitimized until the Bail Reform Act of 1984. However, because our data precede the latter act, they confirm that this act simply reinstitutionalized earlier practice. Meanwhile, our race-specific findings may explain why although this and earlier studies find negligible main effects of race on criminal justice outcomes, black Americans nonetheless perceive more criminal injustice than do whites. In the criminal justice system, as in other spheres of American society, whites receive a better return on their resources, but our findings that the statutory severity of the offense and dangerousness work to the relative disadvantage of white defendants’ challenges conflict and labeling theory's one-dimensional characterization of black defendant disadvantage